Don't know, don't care: Harnessing the power of prior knowledge and motivation to create an effective assignment in an introductory religious studies course - Schwarz, Sarah L. (Teaching theology and religion, 2019)
One of three short companion essays to Terry Shoemaker's "World Religion and Fake News: A Pedagogical Response in an Age of Post-Truth," published in this issue of the journal.